Pengaruh Partisipasi Penyusunan Anggaran terhadap Kinerja Manajer: Peran Kecukupan Anggaran dan Job-Relevant Information sebagai Variabel Intervening - Candra Sinuraya (Jurnal Akuntansi, 2009)
Studies concerned on the relationship between budget-arranging participation and managerial performance are interesting topic for some researchers. However, many of those researches’ result are still indicated inconsistent. Empirically, this study tested the influence of budget adequacy and job-relevant information as variable intervening on the relationship between budget participation and managerial performance. Data were collected through questionnaire and distributed to 900 production managers or chief operational officers or production supervisors at garment and textile companies in West Java and Banten. Meanwhile, questionnaires which had been collected and processed were 239 questionnaires (with responds rate 26,1%). The data were analyzed using structure equation modeling (SEM) of analysis of moment structure (AMOS) program). Results of the study showed that budget participation did not directly influence on managerial performance, job-relevant information did not influence on budget adequacy and budget adequacy did not influence on managerial performance. On the other hand, result indicated that budget participation influenced budget adequacy, budget participation influenced job-relevant information, and job-relevant information influenced managerial performance. Keywords: Budgeting participation, Managerial Performance, Budget Adequcy, Job-Relevant Information, Structure Equation Modeling (SEM), Analysis of Moment Structure (AMOS)